MANAJEMEN PENGEMBANGAN KOMPETENSI DOSEN DI PERGURUAN TINGGI SWASTA - Citra Dewi (Universitas Negeri Malang, 2018)
Abstract: Teacher and educational institutions as an institution that produces of quality educational graduate, the development of lecturer competence is necessary because of the profession needs. The purpose of this study was to analyze the process of pedagogic lecturer competence developing management. This research used qualitative approach by using interviews, observation and documentation. The results of this research are (1) environment analysis of the two universities have strengths, weaknesses, opportunities, and threats, (2)the activities in the strategy construction made formulation team, doing construction of Strategic Planning and socialization of it, (3) the activities carried out in the form of planning; each study program made an annual work program based on the vision and mission of the faculty that implicated in the budget program planning, (4) The activities in the implementation such as training, seminars, workshops, postgraduate program for lecturers, (5) in controlling activities undertaken in those aspects; learning process, research, and lecturer community service and improving the academic position of lecturers within a certain period, but still found lecturer who teach do not suitable with the her/his qualifications, and (6) the activities in evaluating step include evaluation of faculty performance and evaluation of learning although still found some lecturers who are not productive in research and community service. Keywords: management, pedagogic lecturer competence, higher education Abstrak: Tujuan penelitian ini adalah mengetahui dan menganalisis kegiatan pada aspek; (1) analisis lingkungan; (2) perumusan strategi, (3) perencanaan; (4) implementasi; (5) pengawasaan; dan (6) penilaian. Metode penelitian ini melalui pendekatan kualitatif dengan menggunakan teknik wawancara, observasi, dan studi dokumentasi. Kesimpulan hasil penelitian ini adalah (1) dari hasil analisa lingkungan kedua perguruan tinggi memiliki kekuatan, kelemahan, peluang, dan tantangan yang beraneka ragam, (2) kegiatan yang dilakukaan dalam perumusan strategi yaitu pembentukan tim perumus Rensta, melakukan perumusan, dan sosialisasi, (3) kegiatan yang dilakukan dalam perencanaan berupa; pembuatan program kerja tahunan prodi yang didasarkan pada visi dan misi fakultas dituangkan dalam rencana anggaran belanja prodi. (4) Kegiatan dalam implementasi berupa pelatihan, seminar, workshop, serta program studi lanjut bagi dosen, (5) kegiatan pengawasan yang dilakukan berupa monitoring pembelajaran, penelitian namun masih ditemukan dosen yang mengajar tidak sesuai dengan kualifikasi bidang ilmu nya, dan (6) kegiatan yang dilakukan dalam penilaian berupa evaluasi kinerja dan evaluasi pembelajaran yang menunjukkan hasil sesuai dengan kriteria yang diharapkan meskipun masih ditemukan dosen yang tidak produktif dalam penelitian dan pengabdian masyarakat.